2021
DOI: 10.1186/s13195-021-00779-7
|View full text |Cite
|
Sign up to set email alerts
|

Huanglian Jiedu decoction remodels the periphery microenvironment to inhibit Alzheimer’s disease progression based on the “brain-gut” axis through multiple integrated omics

Abstract: Background In recent years, excellent results have suggested an association between the “brain-gut” axis and Alzheimer’s disease (AD) progression, yet the role of the “brain-gut” axis in AD pathogenesis still remains obscure. Herein, we provided a potential link between the central and peripheral neuroinflammatory disorders in AD progression. Methods The Morris water maze (MWM) test, immunohistochemistry, ELISA, ProcartaPlex Multiplex immunoassay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 108 publications
(123 reference statements)
1
30
0
Order By: Relevance
“…24 In addition, HLJDD suppressed gut dysbiosis and the associated Aβ accumulation, controlled neuro-inflammation and reversed cognitive impairment. 2 In our previous study, 25 HLJDD-treated APP/PS1 mice showed better performance than vehicle-treated APP/PS1 mice in the Morris water maze test. Meanwhile, in the spatial exploration test, the crossing platform frequency of HLJDD mice was significantly higher than that of model mice.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…24 In addition, HLJDD suppressed gut dysbiosis and the associated Aβ accumulation, controlled neuro-inflammation and reversed cognitive impairment. 2 In our previous study, 25 HLJDD-treated APP/PS1 mice showed better performance than vehicle-treated APP/PS1 mice in the Morris water maze test. Meanwhile, in the spatial exploration test, the crossing platform frequency of HLJDD mice was significantly higher than that of model mice.…”
Section: Introductionmentioning
confidence: 86%
“…Most of anti-AD drugs have a single molecular target and are mainly acetylcholinesterase inhibitors, which is not an optimal choice for AD patients with multi-pathogenesis. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although initially hypothesized for gastrointestinal disorders [ 102 ], gut microbiome-derived biomarkers have also been considered for psychological and neurodegenerative diseases (i.e., bipolar disorder, multiple Sclerosis, and PD), reporting powerful predictivity and differential diagnosis ability [ 103 , 104 , 105 ]. Regarding AD, promising results have recently been obtained, and Table 1 summarizes the main findings [ 72 , 73 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ] ( Table 1 ). Whilst species of Prevotella and Helicobacter have been shown to be significantly different between APP/PS1 transgenic mice and controls, Actinobacteria and TM7 phylum seem to be more accurate in diagnosing AD when using the triple transgenic mouse model [ 106 , 107 , 109 ].…”
Section: Mainmentioning
confidence: 99%
“…For example, Zhang et al report how gut microbiota composition, serum miRNAs and dietary quality scores can be used together to improve reproducibility and consistency [ 112 ]. In this respect, it would be interesting to investigate whether SCFAs, in combination with other fluid biomarkers, might prove effective in disease diagnosis and clinical monitoring, as some evidence already suggested [ 108 ].…”
Section: Mainmentioning
confidence: 99%
“…Furthermore, omics technologies have already been applied in studies searching for the potential metabolic pathways and integrative biomarkers that would help to understand the link between nutrition, food patterns [ 119 , 120 ] and brain health [ 121 ]. A recent preclinical study with mice, highlighted the roles of neuroinflammation induced by gut dysbiosis and lipid metabolism disorders in Alzheimer’s progression, through an integrated metabolomic approach, showing the potential of omics techniques to understand complex mechanisms [ 122 ]. Also, in relation to the gut brain axis, another study found that a 28-day intermittent fasting regimen improved cognitive deficits in diabetic mice.…”
Section: High-throughput Techniques and Biological Models To Study Om...mentioning
confidence: 99%